The exercise of citizenship at school - Mainardi, Neuza; Teixeira Bicudo Pereira, Isabel Maria (O Mundo da Saúde, 2007)
This article is an invitation to a reflection on pedagogical practice and the position of education professionals for a better exploration of educative work in a healthy environment. The school, although socially recognized as a context favorable to knowledge development, attitudes and abilities, is not satisfactorily contributing for the exercise of citizenship. The paper aims to offer subsidies so that educators can rethink their practices and feel that improve it is always possible and necessary. How to facilitate in an efficient way infantile development aimed at a conscientious and citizenship committed to social health? We conclude that it is in daily experience, in the fulfillment of duties and the fight for rights that a conscientious citizen, healthy and happy may develop and that the school can and must decisively contribute for that to happens, in transdisciplinary work.